Going beyond the Human: Christians and Other Transhumanists. Issue 1 (March 2015) - Cole‐Turner, Ronald
Abstract: Transhumanism is a Christian concept. Although today's transhumanism has secularized the original Christian promise for divinization or theosis by adding evolution and technological progress, Christians should critically re‐take ownership of the role transhumanism plays in the sanctification process.